Kesanggupan Membayar Balik Pinjaman PTPTN: Kajian Kes di Universiti Malaysia Terengganu - Mohamad Sahizam, Musa (2012)
The National Higher Education Fund Corporation (known as Perbadanan Tabung Pendidikan Tinggi Nasional or PTPTN), began on lst July 1997 to provide education loans to students. However, the process of getting students to repay the loans remains an unresolved issue. The general objective of this study was to test the willingness of students to repay their loans, their acceptance of PTPTN's information and student attitudes to repaying their loan. This research also intended to design an instrument to measure the students willingness to repay the PTPTN loan. This research used both quantitative and qualitative methods. First, using stratified simple random sampling, 337 respondents taken from 2,575 students of population at Universiti Malaysia Terengganu. Although 100% of questionnaires distributed to students were returned, 337 (or about 96.3%) of the questionnaires were used in the research analysis based on the numbers required by the research design. Second, in-depth telephone interviews were conducted with 30 students. Pearsons Correlation Test was used to find the relationships between the independent variables and the dependent variable (willingness to repay the loan). Of the five variables tested, four were significantly correlated with willingness to repay the loan. These variables were: 1) student information about PTPTN from media sources, 2) information sharing among peers, 3) a student's attitude and commitment to repay his loans and 4) subjective norms (a student's past and present experience witnessing the situations of those who either repaid or did not repay their PTPTN loans. This research showed that the level of students' willingness to repay the loan was 'moderate" and was influence by a student's employment prospects. This research contributes to improving: 1) management of educational loans, 2) managing students' finances, 3) two-way communication between PTPTN and students, and 4) helping the students' understand how PTPTN works.